Exploring the Transformative Impact of Technological Advancements on English Teachers in Rural Areas - Hajar, Ibnu; Helmiyadi, Helmiyadi; Mawardi, Mawardi; Muntazar, T. (Universitas Muhammadiyah Barru, 2025)
Teachers in urban areas are typically the only ones who can employ such advancements. Fortunately, some English teachers in rural areas in North Aceh, Indonesia, make an unusual effort to integrate technology into their lessons. This fact has not attracted much attention from researchers. This study then attempted to look into how those teachers transform themselves by utilizing technology in the instructional process. This study sheds light on how rural teachers-despite limited resources-adapt and transform their teaching practices through technology. By examining their strategies and challenges, this study provides valuable insights into grassroots-level educational innovation in underserved regions, filling a critical gap in the literature on technology integration in rural contexts. Seven English teachers at six junior high schools in the area participated in this study. The data were collected through semi-structured interviews. The collected data were then analyzed using descriptive qualitative approaches, including data collection, data condensation, data presentation, and conclusion. Data analysis showed that teachers transform themselves through online and offline training, self-directed learning, preparing online learning materials and media, and collaborating with parents, community members, and stakeholders. This study highlights the need for professional development for rural teachers, policy recommendations for improved infrastructure, funding, incentives, and community engagement to bridge the digital divide in education.